Global Lookahead Management (GLM) Protocol for Conservative DEVS Simulation - Jafer, S; Wainer, G (2010 IEEE/ACM 14th International Symposium on Distributed Simulation and Real Time Applications, 2010)
An approach to carrying out asynchronous distributed simulation of multiprocessor message passing architectures is presented. Aiming at achieving better performance on Conservative DEVS-based simulations, we introduce the GLM protocol which borrows the idea of safe processing intervals from the conservative time window algorithm and maintains global synchronization in a fashion similar to the distributed snapshot technique. Under the GLM scheme, a central look ahead manager (LM) exists which is in charge of receiving every LP's look ahead, identifying the global minimum look ahead of the system, and broadcasting it via null messages to all LPs. The simulation is divided into cycles of two phases: Parallel phase and Broadcast phase. The GLM protocol is asynchronous and the central look ahead manager is not expected to be a bottleneck since the only message transmissions involving it take place when all LPs are blocked waiting for permission to advance their LVTs. The results presented in this paper show that the GLM protocol not only significantly reduces the total number of null messages, but it improves the performance and higher speedups are achieved.